1991
DOI: 10.1002/clc.4960140306
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between exercise tolerance and quality of life in angina pectoris

Abstract: Summary:The relationship between exercise tolerance assessed by a conventional exercise stress test using a standard Bruce protocol and quality of life (QoL) was studied in 50 patients with stable angina pectoris (AP). Before the exercise test, patients completed three self-administered QoL questionnaires, the Psychological General WellBeing Index, an Angina-Specific QoL Questionnaire, and Jenkins' Sleep Dysfunction Scale. Total exercise time (r= -0.40) and time until onset ofpain (r= -0.44) were significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 23 publications
1
27
1
Order By: Relevance
“…Correlations were mostly moderate to strong, the exception being the assessment of HB severity in the HB group, where the correlation between physician rating and patient reporting was low. The discrepancies between patientreports and observer-reports are well documented 30,[39][40][41] , and this highlights the need for consolidation of physician examination with patient reporting. 42 For clinical trials, the most important criteria of an instrument is probably its ability to detect small changes over time.…”
Section: Discussionmentioning
confidence: 99%
“…Correlations were mostly moderate to strong, the exception being the assessment of HB severity in the HB group, where the correlation between physician rating and patient reporting was low. The discrepancies between patientreports and observer-reports are well documented 30,[39][40][41] , and this highlights the need for consolidation of physician examination with patient reporting. 42 For clinical trials, the most important criteria of an instrument is probably its ability to detect small changes over time.…”
Section: Discussionmentioning
confidence: 99%
“…These procedures ranged from submaximal cycle ergometry (Massie & Shephard, 1971;Moses et al, 1989) to maximal graded exercise stress tests with assessment of expired gases (Blumenthal et al, 1991;Wiklund et al, 1991). Although studies employing maximal graded tests often report that ~0 , m a x was achieved, in reality it is often difficult if not impossib!e to achieve a verifiable steady-state ~0 , m a x with older adults.…”
Section: Psychological Well-being and Physical Fitnessmentioning
confidence: 99%
“…Twenty one of these studies reported exercise training programs as being associated with positive changes in aerobic capacity/physical fitness, ranging from a 5% increase in V02max (King et al, 1993) to a 16% increase in V0,max (Pierce et al, 1993). Two studies (Segebartt et al, 1988;Wiklund et al, 1991) reported physical fitness assessments associated with a single graded exercise test, and therefore no improvements were noted. Nevertheless, these studies are included in Table 2.…”
Section: Psychological Well-being and Physical Fitnessmentioning
confidence: 99%
“…Little is known about the determinants of health status in patients with cardiovascular disease (5)(6)(7)(8)(9)(10)(11). In particular, the extent to which health status is determined by psychological versus physiological measures of cardiac function is unclear (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%